Jerusalem, Israel/Palästina: Die Ausgrabung im Museum der Erlöserkirche – ein trinationales Projekt - Soennecken, Katja; Serr, Marcel (e-Forschungsberichte des DAI, 2023)
The excavation in the museum took place in the broader context of former GPIA excavations and projects at the Church of the Redeemer. In 2009–2012 the GPIA developed the excavation of the 1970s into an archaeological park called „Through the Ages“. The site was made accessible for visitors and the scientific findings were edited for tourists. In the cloister adjacent to the Church of the Redeemer and the Archaeological Park a museum completes the site. The aim of this research project is to explore the so far unknown medieval strata in the Muristan area. It focusses on the pre-Crusader und Crusader period that is until today basically only known through written sources.